Personal and Cultural Memories in War Tourism - Anita Skelin Horvat ([sic])
The history and memories of past events are relayed through popular culture, the media and the public sphere. City tours organized for tourists can be said to be a special part of popular culture and the public sphere. Since 2006 there has been an organised war tour in the City of Dubrovnik which follows the “routes” of war aggression and the devastation of the town. In this paper, one such specific route The Story about the War is analysed. The main aim of the analysis is to understand the discursive construction and narrative production of memories of war and aggression and how they are embedded in the popularized narrative with a special purpose and target group in mind, namely to inform and to entertain tourists. The personal and collective memories of troubling events and how they are produced and reproduced, and even performed in such a narrative are important elements of the analysis as well. We try to understand how personal memory can be located not only in a place itself but also within a particular narrative and constructed in a specific form (for/with a special purpose) of interpretation of the past events.